HFT-T, a Targeting Nanoparticle, Enhances Specific Delivery of Paclitaxel to Folate Receptor-Positive Tumors - Xu Wang; Jun Li; Yiqing Wang; Kwang Jae Cho; Kim Gloria; Ada Gjyrezi; Lydia Koenig; Paraskevi Giannakakou; Hyung Ju C. Shin; Mourad Tighiouart; Shuming Nie; Zhuo Chen; et al. (2009)
Nonspecific distribution of chemotherapeutic drugs (such as paclitaxel) is a major factor contributing to side effects and poor clinical outcomes in the treatment of human head and neck cancer. To develop novel drug delivery systems with enhanced efficacy and minimized adverse effects, we synthesized a ternary conjugate heparin-folic acid-paclitaxel (HFT), loaded with additional paclitaxel (T). The resulting nanoparticle, HFT-T, is expected to retain the antitumor activity of paclitaxel and specifically target folate receptor (FR)-expressing tumors, thereby increasing the bioavailability and efficacy of paclitaxel. In vitro experiments found that HFT-T selectively recognizes FR-positive human head and neck cancer cell line KB-3-1, displaying higher cytotoxicity compared to the free form of paclitaxel. In a subcutaneous KB-3-1 xenograft model, HFT-T administration enhanced the specific delivery of paclitaxel into tumor tissues and remarkably improved antitumor efficacy of paclitaxel. The average tumor volume in the HFT-T treatment group was 92.9 +/- 78.2 mm(3) vs 1670.3 +/- 286.1 mm(3) in the mice treated with free paclitaxel. Furthermore, paclitaxel tumors showed a resurgence of growth after several weeks of treatment, but this was not observed with HFT-T. This indicates that HFT-T could be more effective in preventing tumors from developing drug resistance. No significant acute in vivo toxicity was observed. These results indicate that specific delivery of paclitaxel with a ternary structured nanoparticle (HFT-T) targeting FR-positive tumor is a promising strategy to enhance chemotherapy efficacy and minimize adverse effects.